Molecular cloning and functional characterization of the shikimate kinase gene from Baphicacanthus cusia - Huang, Yuxiang; Tan, Hexin; Li, Qing; Wu, Xunxun; Guo, Zhiying; Chen, Junfeng; Zhang, Lei; Diao, Yong (Frontiers in Plant Science, 2025)
Baphicacanthus cusia (Nee) Bremek, a perennial herbaceous plant with medicinal properties, has limited genomic insights regarding the genes involved in its indole alkaloid biosynthesis pathway. In this study, the BcSK gene was isolated and cloned from the transcriptome data of B. cusia. The full-length cDNA of BcSK is 1,657 bp, comprising a 265 bp 5’ UTR, a 507 bp 3’ UTR, and an 885 bp ORF encoding 295 amino acids. The exon-intron structure of BcSK consists of four exons and three introns. Bioinformatics and phylogenetic analyses revealed a high degree of homology between BcSK and its counterparts in various plant species. Quantitative real-time polymerase chain reaction (RT-qPCR) analysis showed that BcSK expression was significantly altered under abiotic stress conditions, including methyl jasmonate (MeJA), abscisic acid (ABA), and ultraviolet (UV) radiation. The gene was predominantly expressed in flowers compared to roots, stems, and leaves. Subcellular localization analysis indicated that BcSK is primarily expressed in chloroplasts, confirming that the conversion of shikimic acid to shikimate-3-phosphate occurs in this organelle. Prokaryotic expression and enzyme activity assays demonstrated that the heterologously expressed BcSK protein catalyzed the conversion of shikimic acid to shikimate-3-phosphate. Furthermore, the ectopic overexpression of BcSK in Isatis indigotica significantly enhanced the biosynthetic flux toward indole alkaloids, including indole, indigo, and indirubin. In conclusion, this study identifies and characterizes a novel BcSK gene, providing new insights and potential applications for the metabolic engineering of B. cusia.